PENGARUH PENAMBAHAN FILLER BLOTONG TERHADAP POTENSI CAKING PUPUK MAJEMUK GRANUL - K Kasmadi; Budi Nugroho; Atang Sutandi; Syaiful Anwar (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
The physical quality of NPK fertilizer is very important, good physical quality, as indicated by the low potential of caking and absorption-penetration of water so that NPK fertilizer can be stored for a longer time and easier in handling. In this study, the granulation test used NPK 15-15-15 + 5S formula with the percentage filter pressmud 0%, 60%, 70%, 80%. 90% and 100% in two types of K sources: MOP (KCl) and SOP (K2SO4). Granulation was carried out using the wet granulation method using pan granulator, 2 kg batch-1 capacity, rotation speed 23 rpm and 50o pan slope. The purpose of this study was to determine the effect of filter pressmud addition on the tendency of caking NPK 15-15-15 + 5S products during storage. The results showed that the addition of pressmud filler in the production of NPK fertilizer was obtained: the addition of filter pressmud as a filler in the production of 15-15-15 + 5S NPK fertilizers can reduce the potential of caking by 1.77% -44.31% depending on the formulation of raw materials used.